2008
DOI: 10.1159/000141648
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Double-Blind Study to Investigate the Clinical Efficacy of Adding a Non-Migrating Antimicrobial to a Special Silk Fabric in the Treatment of Atopic Dermatitis

Abstract: Background: A randomized, double-blind study designed to compare the efficacy of DermaSilk® versus a sleeve of similar structure but minus the AEM 5772/5 antimicrobial finish in the treatment of atopic dermatitis (AD). Objective: To evaluate the clinical effect of adding an antimicrobial finish to knitted silk garments on eczema severity and on pruritus in patients with AD. Methods: Thirty patients aged between 3 and 31 years (mean 14.2 ± 7.7) were enrolled. The inclusion criterion was that the patients presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 26 publications
(13 reference statements)
0
30
0
Order By: Relevance
“…In the study by Stinco and colleagues, 339 both the severity of eczema under the area covered by the fabrics and participant-assessed itching were significantly better with DermaSilk fabric than with the same fabric without the impregnated antimicrobial. The difference in the pruritus score was 1.88 SD ± 1.7 (p < 0.0001) on a 10-point VAS and the difference in severity measured by the SCORAD index was a reduction of 10.98 SD ± 11.9 (p < 0.0001) more in the DermaSilk group than in the DermaSilk without antimicrobial group.…”
Section: Benefitsmentioning
confidence: 92%
See 3 more Smart Citations
“…In the study by Stinco and colleagues, 339 both the severity of eczema under the area covered by the fabrics and participant-assessed itching were significantly better with DermaSilk fabric than with the same fabric without the impregnated antimicrobial. The difference in the pruritus score was 1.88 SD ± 1.7 (p < 0.0001) on a 10-point VAS and the difference in severity measured by the SCORAD index was a reduction of 10.98 SD ± 11.9 (p < 0.0001) more in the DermaSilk group than in the DermaSilk without antimicrobial group.…”
Section: Benefitsmentioning
confidence: 92%
“…The two studies on DermaSilk by Koller and colleagues 338 and Stinco and colleagues 339 reported that there were no adverse events during the study periods. The trial by Fontanini and colleagues 340 did not report information about adverse events.…”
Section: Harmsmentioning
confidence: 95%
See 2 more Smart Citations
“…The review found two small RCTs of silk clothing, 353,354 but these were too small (22 and 30 participants, respectively) and of too limited a duration (12 and 4 weeks, respectively) to be able to inform clinical practice. The NIHR HTA systematic review of treatments for eczema 224 has now been updated as described in the first section of this report (see Chapter 1), but no additional RCTs on the use of silk clothing have been identified.…”
Section: What Did This Study Add?mentioning
confidence: 99%